Size-sex and sex-age structure in populations of Far-Eastern flounders (Pleuronectidae) - Yury P. Diakov (Известия ТИНРО)
Cited and archive data on sex ratio and its changes with age are generalized for 28 species of flounders from the Far-Eastern Seas of Russia belonged to the family Pleuronectidae. Spatial and temporal variations of their size-sex and sex-age structure are considered by species. Among the flounders, the portion of females increases with age and reaches 100 % in the largest and eldest classes. Populations of the western Bering Sea (pacific black halibut, arrowtooth flounder, yellowfin sole, and northern rock sole) and the eastern Okhotsk Sea (pacific black halibut, yellowfin sole, flathead sole, alaska plaice, and starry flounder) are distinguished by the maximum length and age with the sex ratio 50% : 50%. Male and female mortality varies, as well, between the populations. For the common species, as yellowfin sole, alaska plaice, sakhalin sole, flathead sole, starry flounder, and some others, the maximal body length and age are observed in the eastern Okhotsk Sea, but the minimal limits of the size and age are observed in the northern and western parts of the Okhotsk Sea.